Challenges, Strategies and Process: an Empirical Study on Mental Health: Examining the Challenges and Strategies in Implementing Mental Health Policies (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Mental health strategy is a formed situated of qualities,standards and destinations for making strides mental health and lessening thetrouble of mental clutters in a people. It demarcates a vision for time andserves to create a model for movement. Arrangement likewise states the level ofnecessity that a legislature allocates to mental health in connection to otherhealth and social strategies. Arrangement is usually figured to blanket a longperiod, e.g. 5 to 10 years.